MARI MENCINTAI BAHASA INDONESIA - Riniwati Riniwati (Universitas Tidar, 2015)
A language has a very important role in humanâ€™s life. Besides, a language reflects the human personality. Therefore it needs responsibility, care and politeness in using Indonesian language. The element of appropriatenessÂ is very needed as the way to appreciate Indonesian language as language of our nation.Keywords: a language, responsibility, appropriateness